A Pirate too Needs to be Heard: Procedural Compromises in Online Copyright Infringement Cases in the UK - Poorna Mysoor (Laws, 2014)
Online copyright infringement is one of the toughest challenges the content industry has faced in the twenty first century. Article 8(3) of the Information Society Directive, implemented under section 97A of the UK Copyright, Designs and Patents Act, 1988, provides an injunctive remedy in response to such online infringement. Given the elusive nature of the website operators and the sheer number of their users, rights owners have turned to the Internet Service Providers (ISPs) to implement the injunctions granted under section 97A to block websites with infringing content. In their battle to keep pace with online infringers, the UK courts have permitted significant compromises to the procedures while granting these injunctive blocking orders. One of the pioneers in this line of cases in the UK is the Pirate Bay case (TPB case), which ruled as a matter of law that the procedure under Section 97A does not require the alleged infringers to be made parties to those proceedings. TPB case also marks the trend of the ISPs consenting to an order of injunction, and not defending the proceedings. This has resulted in the absence of any adverse party in the proceedings under section 97A. This threatens the basic tenets of procedural fairness and propriety, having adverse consequences on both the substantive and procedural aspects, evident in the cases that followed TPB case. This article examines the aspects of the judgment in TPB case that led to these procedural compromises, whether it had any basis in the pre-existing case law, what the nature of an injunction under section 97A is and how the subsequent line of cases have followed TPB case as a precedent. It further explores the adverse consequences of the procedural compromises and whether any safeguards are available against such compromises.